National policy responses to address loneliness: A global scoping review of 194 WHO member states - Goldman, Nina; Alemdar, Melek; Megges, Herlind; Matsumoto, Naka; Schoenmakers, Eric; van den Berg; Pauline; Lasgaard, Mathias; Christiansen, Julie; Junttila, Niina; Goldman, Andreas; Draxl, Debora; et al. (Elsevier, 2026)
Background
Loneliness is associated with adverse physical and mental health outcomes. It affects individuals across all age groups and geographical regions.
Objective
To characterise the extent that WHO Member States address loneliness, social isolation and social connection through national policies.
Methods
We searched government websites using key terms. A matrix was used to extract data, followed by in-depth document analysis.
Results
By February 2025, only eight WHO Member States (Denmark, UK (England, Scotland, Wales), Finland, Germany, Netherlands, Sweden, Japan, USA) had policies directly addressing loneliness, social isolation or social connection. Policymakers validated the findings. Common policy aims included building a more connected society, addressing loneliness as a wider societal challenge rather than just an individual issue, and supporting both individuals and organisations to manage loneliness. Key recommendations in these policies often highlighted the need to increase knowledge through research, raise public awareness to reduce stigma, promote cross-sectoral collaboration, integrate loneliness into government policy and implement community-based approaches. National policies emerged following societal activism, initiatives from government departments or a large-scale research project.
Conclusion
Various policies are in place to help address loneliness at the national level. To maximise impact, policies require adequate funding. To date, none of the national policies had undergone rigorous evaluation concerning their effectiveness. This review highlights the growing political focus on loneliness and provides a starting point for those seeking to understand, develop or strengthen national strategies to address loneliness, social isolation or social connection.